Optimalisasi Sistem Database sebagai Pilar Penguatan Sistem Informasi Manajemen di Era Transformasi Digital Modern - Putri Newa Glenda Azra; Maerani Ikwanda; Noviana Poernama Sari; Tiffany Wahidah Prameswari; Fachmi Tamzil (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
As the complexity of modern web applications continues to increase—particularly with the rise of Single-Page Applications (SPAs)—the need for effective monitoring mechanisms becomes more critical to support fast and accurate debugging processes. One promising approach is the implementation of a monitoring system based on Database Management Systems (DBMS), which allows for systematic logging and tracking of execution data within the application’s runtime environment. This study aims to explore the role of DBMS in supporting bug reproduction, a process that involves recreating a previously encountered bug by collecting real-time information such as activity logs, event traces, and environmental variables. The research method includes the development of a monitoring prototype integrated into a web application, where all runtime data is stored in a centralized database. Experimental evaluations were conducted on large-scale web applications to assess the system’s effectiveness in detecting and reproducing bugs. The results indicate that DBMS-based monitoring significantly improves debugging efficiency by providing contextual execution data that would otherwise be undocumented. Case studies involving the implementation of database systems like MySQL and SQLite in mobile applications demonstrated improvements in both reliability and data access speed for log management. These findings show that integrating monitoring with DBMS contributes meaningfully to maintaining software quality. However, this integration also introduces technical challenges, such as heavy logging loads, potential latency, and data security concerns. To address these issues, this study recommends optimization strategies including caching mechanisms, asynchronous I/O operations, and the adoption of cloud-native architectures to enhance system scalability and performance. By applying these approaches, bug reproduction can be performed more quickly, accurately, and efficiently—ultimately supporting the development of robust and reliable web applications in today’s digital era. This research highlights the importance of runtime observability and structured monitoring as key elements in modern software maintenance and debugging workflows.